Introduction. Enseigner et apprendre les humanités numériques : des savoirs recomposés ? - Laurent Tessier; Michaël Bourgatte (Humanités Numériques)
Over the last few decades, Digital Humanities have contributed to renewing research practices and thus to reconstructing knowledge in the Humanities, a field that breaks down in France into Literature, Languages and Human and Social Sciences. Organised as an international movement of researchers engaged in the usage of technologies in the Humanities, they have taken a growing place in the contemporary scientific landscape. If their development is well documented, it is surprising to note the small number of works devoted to the teaching and learning of Digital Humanities. In this article we test different hypotheses to explain this lack of visibility and suggest that there is a specific pedagogy of Digital Humanities, with its teaching and learning practices, as well as its theoretical and ideological positions.